The Axl-Regulating Tumor Suppressor miR-34a Is Increased in ccRCC but Does Not Correlate with Axl mRNA or Axl Protein Levels - Fritz, Helena K. (PLoS One, 2015)
BACKGROUND: High expression of the receptor tyrosine kinase Axl is associated with poor prognosis in patients with Renal Cell Carcinoma (RCC), the most common malignancy of the kidney. The miR-34a has been shown to directly regulate Axl in cancer cells. The miR-34a is a mediator of p53-dependent tumor suppression, and low expression of miR-34a has been associated with worse prognosis in several cancers. Our aim was to elucidate whether miR-34a or the other members of the miR-34 family (miR-34b/c) regulate Axl in RCC. METHODOLOGY AND RESULTS: Using western blot, flow cytometry, and RT-qPCR, we showed that Axl mRNA and protein are downregulated in 786-O cells by miR-34a and miR-34c but not by miR-34b. A luciferase reporter assay demonstrated direct interaction between the Axl 3’ UTR and miR-34a and miR-34c. The levels of miR-34a/b/c were measured in tumor tissue in a cohort of 198 RCC patients, and the levels of miR-34a were found to be upregulated in clear cell RCC (ccRCC) tumors, but not associated with patient outcome. Neither of the miR-34 family members correlated with Axl mRNA, soluble Axl protein in serum, nor with immunohistochemistry of Axl in tumor tissue. In addition, we measured mRNA levels of a known miR-34a target, HNF4A, and found the HNF4A levels to be decreased in ccRCC tumors, but unexpectedly correlated positively rather than negatively with miR-34a. CONCLUSIONS: Although miR-34a and miR-34c can regulate Axl expression in vitro, our data indicates that the miR-34 family members are not the primary regulators of Axl expression in RCC.